The developmental model of sport participation: 15 years after its first conceptualization - Côté, J.; Vierimaa, M. (Science & Sports, 2014)
The Developmental Model of Sport Participation (DMSP) is a model of athlete development which has been comprehensively researched and refined over the last 15 years. The DMSP is based upon theoretical and empirical data and describes the processes, pathways, and outcomes associated with sport development throughout childhood and adolescence. Côté, Lidor, and Hackfort (in 2009) proposed seven postulates associated with the different pathways of the DMSP. More specifically, five postulates focus on the influence of sampling and deliberate play on youth's participation, performance, and personal development in sport and two postulates focused on important transitions. The purpose of the present article is to systematically grade the quality of empirical evidence supporting each of these seven postulates, and provide recommendations for best practice to help guide sport policy in each of these areas.